Enhanced Recovery After Surgery for Advanced Ovarian Cancer: A Systematic Review of Interventions Trialed. Issue 6 (1st July 2017) - Lindemann, Kristina; Kok, Peey-Sei; Stockler, Martin; Jaaback, Ken; Brand, Alison
Abstract : Objectives: We sought to summarize the evidence for interventions aiming at enhanced recovery after surgery (ERAS) in ovarian cancer through a systematic review. Methods: We searched MEDLINE, EMBASE, and The Cochrane Library for studies testing ERAS interventions in patients undergoing surgery for ovarian cancer. Study selection and data extraction were done independently by 2 reviewers with disagreements resolved by discussion with a senior, third reviewer. Results: We identified 25 studies including 1648 participants with ovarian cancer. Nine observational studies addressed ERAS protocols. Four of them were prospective, and 3 included historical controls. The other 16 studies reported single interventions, for example, early feeding, omission of pelvic drains, early orogastric tube removal, Doppler-guided fluid management, and patient-controlled epidural analgesia. Early feeding protocols were tested in 7 of the 12 randomized trials. Early feeding appeared to be safe and was associated with significantly faster recovery of bowel function. Conclusions: Few studies have specifically studied ERAS interventions in ovarian cancer. All studies on protocols including multiple interventions were susceptible to bias. Early feeding is the intervention that is best supported by randomized trials. Application of evidence for ERAS derived from nonovarian cancer is challenged by the differences not only in the scope of surgery but also in ovarian cancer patients' comorbidities. Postoperative morbidity is particularly high in these patients because of their poor nutritional status, perioperative fluids shifts, and long operating times. These patients may also show excessive response to surgical stress. Innovative, randomized trials are needed to reliably determine the feasibility, safety, and effectiveness of specific ERAS interventions in ovarian cancer.